Annual acoustic dynamics are associated with seasonality in a monsoon tropical forest in South Vietnam - Alexey Opaev (Elsevier, 2021)
We studied the annual dynamics of the biotic component of the acoustic environment in a lowland monsoon tropical forest. The study was conducted in Nam Cat Tien National Park (southern Vietnam) from January 2013 to January 2014. We placed an autonomous recorder at the Nam Cat Tien ecosystem flux observation station at a height of 35 m. For the analysis, we selected 1–4 5-min recordings per day collected at 5.30 a.m., 12.00 a.m., 4.00 p.m., and 8.00 p.m. For each recording, we calculated four acoustic indices: the acoustic complexity index (ACI), the bioacoustic index (BIO), the acoustic diversity index (ADI) and the acoustic evenness index (AEI). These indices had roughly similar annual dynamics and peaked from May to August (i.e., immediately before the wet season and in the wet season). We then related the four acoustic indices to the daily values of the following meteorological variables: air temperature, air relative humidity, solar radiation, and precipitation sum. The BIO, ADI and AEI were most influenced by daily average humidity. We therefore concluded that humidity rather than precipitation, temperature or radiation was the best predictor of the annual dynamics of acoustic activity in Nam Cat Tien. The increase in humidity was apparent several months before the major rains began in 2013 (i.e., before the wet season). We suggest that future ecoacoustics studies in the tropics should give greater consideration to humidity as a variable determining the acoustic activity of local fauna.